Turkey : Rural Finance Study, Volume 2. Expanded Report - World Bank (Washington, DC, 2013)
Over the past five years in Turkey, the agricultural and rural sector has seen substantial change in transfer policies which now place greater emphasis on improved equity and investment. These have been summarized in the earlier World Bank "Review of the Impact of the Reform of Agricultural Sector Subsidization (2004), and "Policy and Investment Priorities for Agricultural and Rural Development" (2005). Currently, the structural changes in the agricultural sector and rural employment generation in response to labor shedding in the agricultural sector are key challenges to which Turkey is responding in the design of and agricultural and rural development strategy. However, the impact of government transfers and public investment policies in the rural sector will be limited unless the supply of, access to, and demand for rural financial services is significantly increased. For these reasons, the Turkey Rural Finance study (RFS) seeks to establish a policy agenda for the Government of Turkey (GOT) in order to contribute to the effort of renewed growth of the rural financial system after a period of prolonged decline. In order to inform this policy agenda, the study also has aimed at portraying the situation of rural financial markets in Turkey and determining the factors influencing the use of financial services by rural households and the constraints affecting the availability of financial services in rural areas. The findings and measures recommended by this study are also important for Turkey's on-going rural sector dialogue with the European Commission (EC), as increased access of small rural enterprises to financial services is desired for improved absorption by these enterprises of EC funding under the Instrument for Pre-Accession programs in rural areas. The findings of the RFS, based on two surveys of rural households and financial intermediaries carried out in 2004 and on other financial data compiled in 2005, reveal that rural financial markets perform relatively poorly, leading to low incidences in the use of financial services by rural households and therefore limiting their ability to take advantage of growth opportunities and/or accumulation of assets. For example while the agricultural sector accounts for roughly 10-15 percent of GDP, it receives only 5 percent of all bank loans. Based on the survey of rural households, over 70 percent of rural households were found to be credit constrained, and only 9 percent of surveyed rural households reported making investment outlays in 2004.